The current and expected environmental effects of excessive groundwater withdrawal in Eastern Section of Wadi Al-Shati (Ashkeda-Bergen) - A. Ahmad Naji; M. Abdulrahman Inweer (Journal of Pure & Applied Sciences, 2022)
Water is the origin of life for all creatures; It helps people secure their urban and agricultural needs to survive. Agriculture is considered as one of the dominant activities in Libya which consumes a lot of water. In Wadi Al-Shati area, 65%-97% of groundwater is consumed in agriculture, because of the absence of other water sources in the area, such as water bodies, rainwater or treated water. This groundwater is pulled out by wells, whether they are artesian or ordinary wells - often drilled at random and without study. This research studied the current and expected future environmental effects of the excessive consumption of groundwater in the eastern section of Wadi Al-Shati  and its impact on living organisms and their survival. After reviewing previous studies, the data of the groundwater level monitoring wells in the region was studied and analyzed, and the negative environmental changes occurred in the area were observed, such as the drought of palm oases, the decline of agricultural lands, the salinization of the soil, the depletion of many natural water springs, the sand creeping, the decrease in the numbers and the disappearance of many types of birds and wild animals which was teeming with the area. Accordingly, the study concluded that the areas  witnessing intensive agricultural activity are subject to greater rates of decline in their groundwater levels, such as the Ashkedah Agricultural Project with a falling rate of (0.662 m/year), Um Al-Jadawill Project (0.981 m/year) and the Aril Agricultural Project (0.690 m/year)more than other areas. The statistical analysis of the data of the groundwater level monitoring wells in the region showed that the groundwater level is declining in the future, Therefore; the study recommended the necessity of stopping random drilling of wells, maintenance of  artesian well heads, or permanently closing them, following regulated agricultural irrigation methods and continuing to observe monitoring wells.